RNA binding proteins as regulators of immune cell biology. (11th September 2015) - Newman, R.; McHugh, J.; Turner, M.
Summary: Sequence‐specific RNA binding proteins (RBP) are important regulators of the immune response. RBP modulate gene expression by regulating splicing, polyadenylation, localization, translation and decay of target mRNAs. Increasing evidence suggests that RBP play critical roles in the development, activation and function of lymphocyte populations in the immune system. This review will discuss the post‐transcriptional regulation of gene expression by RBP during lymphocyte development, with particular focus on the Tristetraprolin family of RBP.